2019
DOI: 10.1038/s41422-019-0225-9
|View full text |Cite
|
Sign up to set email alerts
|

Protein C receptor is a therapeutic stem cell target in a distinct group of breast cancers

Abstract: Breast cancer is a heterogeneous disease. In particular, triple-negative breast cancer (TNBC) comprises various molecular subgroups with unclear identities and currently has few targeted treatment options. Our previous study identified protein C receptor (Procr) as a surface marker on mammary stem cells (MaSCs) located in the basal layer of the normal mammary gland. Given the possible connection of TNBC with basal layer stem cells, we conducted comparative analyses of Procr in breast cancers of mouse and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 43 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…Examining the basal cell data in more detail identified 9 receptors (Gpc1, Procr, Fzd7, Itga5, Ldlr, Tlr2, Lrp6, Ephb1, and Tfrc) and 8 ligands (Tgfa, Ngf, Col5a2, Il11, Col4a2, Jag1, Col18a1 and Hspg2) at least twofold down-regulated at 18 months ( Supplementary Data 8). Notably, many of these top downregulated ligands and receptors are known to be important in maintenance of normal mammary basal stem cells and are implicated in basal-like and triple negative breast cancer [43][44][45][46][47][48][49][50][51] .…”
Section: Resultsmentioning
confidence: 99%
“…Examining the basal cell data in more detail identified 9 receptors (Gpc1, Procr, Fzd7, Itga5, Ldlr, Tlr2, Lrp6, Ephb1, and Tfrc) and 8 ligands (Tgfa, Ngf, Col5a2, Il11, Col4a2, Jag1, Col18a1 and Hspg2) at least twofold down-regulated at 18 months ( Supplementary Data 8). Notably, many of these top downregulated ligands and receptors are known to be important in maintenance of normal mammary basal stem cells and are implicated in basal-like and triple negative breast cancer [43][44][45][46][47][48][49][50][51] .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Rossotti et al ( 57 ) reported DNA immunization-raised EGFR nanobodies with improved functionality compared to protein immunization-raised nanobodies. Nanobodies targeting EGF ( 58 ), HER2 ( 59 , 60 ), CAIX ( 61 ), death receptor 5 (DR5) ( 62 , 63 ), c-Met ( 64 , 65 ), HGF ( 66 ), AgSK1 ( 67 ), mesothelin ( 68 ), proteasome activator complex PA28 ( 69 ), ephrin receptor A4 (EphA4) ( 70 ), CEA-cell adhesion molecule-6 (CEACAM6) ( 71 ), mitochondrial translation elongation factor (TUFM) ( 72 ), protein C receptor ( 73 ), Wnt receptors (LRP5/6) ( 74 ), and CD33 ( 75 ) have also demonstrated delayed tumor growth.…”
Section: Nanobodies As a Cancer Therapeuticsmentioning
confidence: 99%
“…Whether PROCR plays an analogous role in normal human breast tissue remains unknown but its expression is confined to the basal layer. 6 Extending their study to specimens from breast cancer patients, Wang et al next showed that PROCR was highly expressed in approximately half of TNBCs in their patient cohorts. Notably, there was an inverse correlation between PROCR hi and BRCA1 mutant TNBCs.…”
mentioning
confidence: 98%
“…The study by Wang et al has significantly clarified this area through identification of PROCR as a specific marker of CSCs in TNBCs. 6 They first compared the tumor-initiating capacity of Procr + tumor cells in three different mouse models of breast cancer. Although Procr was expressed on a small subset of tumor cells in all models, it specifically enriched for CSCs in the Wnt1driven transgenic model, which harbors an expanded population of stem-like cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation